THE FACTOR INFLUENCING IMPULSE BUYING OF SAM RATULANGI UNIVERSITY STUDENTS AT MR D.I.Y MANADO TOWN SQUARE - Yufika Injillia Poniskori; Maryam Mangantar; Fitty Valdi Arie (Universitas Sam Ratulangi, 2022)
Abstract: The development of household population that increasingly growing every year makes retail business competes to fulfil household needs. In an effort to maintain their position in the market, retailers must learn several marketing strategies and what factors can attract customer’s impulse buying intention and MR D.I.Y is one of the modern retail stores that provide household needs. The intention of this study is to analyse and identify what are the factors that influencing the impulse buying of Sam Ratulangi Students at MR D.I.Y Manado Town Square. The respondents of this study is 100 students that have experience in MR D.I.Y Manado Town Square using convenience sampling. Confirmatory Factor Analysis is used to analyse the data in this research. There are 14 factors included in this analysis and the result shows that all 14 factors are correlated with each other. From the factoring process, there are 3 factors formed as a result which are: Customer purchase intention factors, Environmental factors and Situational factors.